Interaction between arbuscular mycorrhizal fungi and Bacillus spp. in soil enhancing growth of crop plants - Anuroopa Nanjundappa (Fungal Biology and Biotechnology, 2019)
Abstract Soil microorganisms play an important role in enhancing soil fertility and plant health. Arbuscular mycorrhizal fungi and plant growth promoting rhizobacteria form a key component of the soil microbial population. Arbuscular mycorrhizal fungi form symbiotic association with most of the cultivated crop plants and they help plants in phosphorus nutrition and protecting them against biotic and abiotic stresses. Many species of Bacillus occurring in soil are also known to promote plant growth through phosphate solubilization, phytohormone production and protection against biotic and abiotic stresses. Synergistic interaction between AMF and Bacillus spp. in promoting plant growth compared to single inoculation with either of them has been reported. This is because of enhanced nutrient uptake, protection against plant pathogens and alleviation of abiotic stresses (water, salinity and heavy metal) through dual inoculation compared to inoculation with either AMF or Bacillus alone.